La población de las zonas urbano marginales de Lima y la demanda por educación universitaria estatal periodo 1980-2010 - Ospino Edery, Ysaac (2012)
The concentration of populations in marginal urban areas, are in a process of relative growth, so we have the second half of the twentieth century, as a result of migration that have their origin in search of better living conditions (security, education, health, employment, housing, etc.), were established dozens of settlements that later became developments and today some prosperous and thriving districts (San Juan de Lurigancho, San Martin de Porres, San Juan de Miraflores Ventanila, Los Olivos, etc), districts which come most of the leading candidates to national universities of our capital, as well as to form the largest proportion of the student population. So we have a predominant factor for the study of the evolution of the demand for university education constitutes State the incidence of the concentration of population in urban fringe areas, given its influence on the behavior of the educational system enrollment at all levels, a situation that can be seen with the highest incidence in the city of Lima.